Effects of vertical spatial variability on supported excavations in sands considering multiple geotechnical and structural failure modes. (March 2018) - Luo, Zhe; Li, Yixiang; Zhou, Shunhua; Di, Honggui
Abstract: In this paper, a probabilistic assessment of supported excavations in spatially varied sands is presented. Random finite element modelling (RFEM) is performed to simulate excavation-induced responses. A procedure for automating the Monte Carlo simulation is developed to facilitate the RFEM. The effects of soil vertical spatial variability on several major geotechnical and structural failure modes, including geotechnical ultimate failure, geotechnical serviceability failure, wall bending failure, wall shear failure, and strut buckling failure, are explicitly investigated. This study demonstrates the importance of addressing the spatial variation of soil properties by considering multiple failure modes for complicated soil-structural interaction problems.